Beyond the Tip of the Iceberg: Using Systems Archetypes to Understand Common and Recurring Issues in Sports Coaching - McLean, Scott; Read, Gemma J. M.; Hulme, Adam; Dodd, Karl; Gorman, Adam D.; Solomon, Colin; Salmon, Paul M. (Frontiers in Sports and Active Living, 2019)
Systems thinking, a fundamental approach for understanding complexity is gaining traction in sport science. Systems archetypes (SAs) describe common recurring patterns of system behaviours and explain the systemic influences on behaviour. SAs look at the deeper levels of systemic structure by identifying what creates system behaviours, which supports the development of interventions to identify and resolve problem sources. Four commonly used SAs were used to explain the dynamics underpinning recurring issues for coaching in sport: Fixes that Fail, Shifting the burden, Drifting goals, and Success to the successful, using football specific examples. The SAs models were built, refined and validated by seven subject matter experts including experienced football researchers, systems thinking experts, an international football coach, a skill acquisition specialist, and an exercise scientist. The findings show that SAs fit well in the football coaching context, providing further evidence that a complex system thinking approach is required when considering football performance and its optimisation. The developed SAs identify the factors that play a role in recurring issues in football coaching and highlight the systemic structures that contribute to the issues. Systemic problems often arise in football when quick fixes are attempted. Whereas, improvements to system behaviour usually require a delay after the implementation of the appropriate corrective action. The SAs developed in the current study also provide practical templates of common problems in football that can be used to prompt discussions around how to avoid common, but ineffective interventions and instead make sustainable improvements across multiple aspects of football performance.